2010
DOI: 10.1590/s0104-42302010000300017
|View full text |Cite
|
Sign up to set email alerts
|

Pólipos da vesícula biliar. Como e quando tratar?

Abstract: objectIve. The objective of this study was to determine the correct therapeutic management for patients with gallbladder polyps (GPs), what type of surveillance should be employed and how to differentiate between benign and malignant polyps in addition to also to providing reassurance in cases of "cancerophobia". Study design: This was a 5-years retrospective study. Location: The study was conducted at a Surgery Department at the Hospitais da Universidade de Coimbra. Population: We analyzed all patients operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 7 publications
0
26
0
6
Order By: Relevance
“…[4] In the majority of publications in which the ratio is calculated, the incidence is more prevalent in men. [15] The sex ratio and age at the time of diagnosis of gallbladder polyps was 1.15 to 1 (male to female). [46]…”
Section: Incidence Of Gallbladder Polypsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] In the majority of publications in which the ratio is calculated, the incidence is more prevalent in men. [15] The sex ratio and age at the time of diagnosis of gallbladder polyps was 1.15 to 1 (male to female). [46]…”
Section: Incidence Of Gallbladder Polypsmentioning
confidence: 99%
“…There are descriptions of polyps that protrude greatly obstructing the cystic canal or the primary biliary ducts, causing acute cholecystitis or obstructive jaundice, but these are very rare complications. [1]…”
Section: Symptomatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Bagnoli et al14 verified the expression levels and correlation of aromatase, matrix metalloproteinase 2 (MMP-2), matrix metalloproteinase 9 (MMP-9) and CD44 in ductal carcinoma in situ (DCIS) and infiltrating ductal carcinoma (IDC) when both are found in the same breast and conclude that aromatase through local estrogen synthesis in breast tissue plays an important role in breast carcinogenesis, mainly influencing MMP-2 and MMP-9 which are important participants in tumor cell invasion and dependence of their connection to CD44 for action. Matos et al49 present a series of 93 consecutive patients who had elective surgery for known gallbladder polyps, treated from January 2003 to December 2007 and claim that cholecystectomy is the appropriate surgical treatment for gallbladder polyps, when removal is warranted. Saad et al50 have previously suggested that pretreatment levels of CA 19-9 correlate with overall survival among patients with advanced pancreatic cancer treated with gemcitabine; they sought to confirm the prognostic role of the pretreatment level of CA 19-9 and found further evidence in favor of the concept.…”
Section: Reviewmentioning
confidence: 99%
“…Macedo et al60 determined the occurrence of hepatopulmonary syndrome in cirrhosis patients who are candidates for liver transplantation and found a high prevalence of the syndrome, which however did not correlate with any of the variables analyzed. Matos et al49 present a series of 93 consecutive patients who had elective surgery for known gallbladder polyps, treated from January 2003 to December 2007 and claim that cholecystectomy is the appropriate surgical treatment for gallbladder polyps, when removal is warranted. The etiology of acute pancreatitis cannot be found by clinical, biological and imaging investigations in 30% of these cases.…”
Section: Reviewmentioning
confidence: 99%